Politeness on Public Signs in Japanese And Indonesian Train Cars - A Study Of Linguistic Landscape - Mubarok, Muhammad Habib; Hayati, Novia; Haristiani, Nuria (Universitas Negeri Semarang, 2024)
The study reports on the comparison of the esxpressions of politeness used in Japanese and Indonesian train cars. It aims to compare how politeness is expressed and in what situations or contexts politeness patterns are formulated on public signs in mobile public space, specifically inside Japanese and Indonesian train cars. This research is conducted under the framework of Linguistic Landscape approach, involving 36 photos of train cars signs in Japanese (19 photos) and in Indonesian (17 photos). This descriptive qualitative study analyzes signs by involving three types of public signs, including prohibitions, warnings, and instructions. The research results in some findings as follows. First, politeness marker in Japanese in any types of public signs of train cars involves the expressions kudasai or 'please' while that in Indonesian includes the use of the prefix 'di-' and the addition of lexical item of 'Mohon'. Second, in Japanese train cars signs, direct expressions appear almost in all types of signs but still using politeness, and explicitness is applied based on the situational needs of the signs, rather than the types of the signs. Similarly, in Indonesian train car signs, direct expressions appear in all types of signs and all signs use two types of politeness markers (lexical item of 'mohon' and the prefix 'di-'). The study found that he degree of politeness in sign expressions varies depending on the situation. Signs indicating danger or threats are typically less polite but more explicit, while those in regular areas are more polite but less explicit. This variation is evident in warning and instructional signs where the severity of the situation dictates the level of politeness and explicitness.